Rozumienie Rosji jako zadanie dla teorii polityki - Bäcker, Roman (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2008)
It is frequently beyond many researchers’ abilities to understand Russia, whether as a whole or only a part. This can be exemplified by many Sovietologists’ failure to forecast the implosion of one of the greatest superpowers at the end of the 20th century. The present paper does not attempt to present a comprehensive discussion of all the possible categories that would facilitate understanding Russia. The latter can only be one’s goal and task and can never be wholly completed. The fundamental purpose of this text does not involve the comprehensive presentation of a range of issues which can never be presented in an exhaustive manner. It is much more important to show a certain way of thinking based on two prerequisites. Firstly, it is necessary to critically consider the semantic range of every word and every category used to explain any social phenomenon. Secondly, it is necessary to account for the territorial limitations (related to structure and awareness) of each notion.